Bright Luminescence from Nontoxic CsCu2X3 (X = Cl, Br, I) - Roccanova, Rachel; Yangui, Aymen; Seo, Gijun; Creason, Tielyr D; Wu, Yuntao; Kim, Do Young; Du, Mao-Hua; Saparov, Bayrammurad (ACS materials letters, 2019)
Inexpensive and highly efficient luminescent materials based on multinary halides have received increased attention in recent years. Among those considered most promising are the perovskites such as CsPbX3 because of their highly efficient and tunable emission through precise control of chemical composition and nanostructuring. However, the presence of the toxic heavy metal Pb and relatively poor stability are among the major challenges for the introduction of lead-halide-based materials into the marketplace. Here, we report the optical properties of nontoxic and highly emissive one-dimensional (1D) all-inorganic halides CsCu2X3 (X = Cl, Br, I) and their mixed halide derivatives, which also show improved thermal and air stability. Photoluminescence (PL) measurements show tunable bright room temperature emission from green to yellow with photoluminescence quantum yields ranging from 0.37 (CsCu2Cl1.5Br1.5) to 48.0% (CsCu2Cl3). Temperature- and power-dependent PL measurements suggest that the emission results from self-trapped excitons induced by strong charge localization and structural distortions within the lD ribbon structure.